Bianchi Type-I Universe with wet dark fluid - Singh, T.; Chaubey, R. (My University, 2008)
The Bianchi Type-I Universe filled with dark energy from a wet dark fluid has been considered. A new equation of state for the dark energy component of the Universe has been used. It is modeled on the equation of state p = γ/(ρ - ρ*) which can describe a liquid, for example water. The exact solutions to the corresponding field equations are obtained in quadrature form. The solution for constant deceleration parameter have been studied in detail for both power-law and exponential forms. The cases γ = 1 and γ = 0 have also been analysed.
Keywords: Bianchi-type universe; Cosmological parameters; Wet dark fluid